European patterns of labour market entry : a dichotomy of occupationalized vs. non-occupationalized systems? - Gangl, Markus [Verfasser] (My University, 2001)
"Many recent comparative studies of school-to-work transitions have revolved around the notion of an institutional dichotomy of transition arrangements that distinguishes the occupational labour markets of countries exhibiting extensive systems of vocational training and apprenticeships from the organizational markets found in countries with less integrated education and employment systems. This study scrutinizes this idea by assessing the extent to which patterns of labour market entry in twelve European Union countries empirically conform to the expected dichotomy. Based on cluster and discriminant analyses, three rather than two typical patterns emerge from the analyses: first, the continental European countries running extensive vocational training systems; second those Northern European countries lacking such systems, and finally, a homogeneous set of Southern European countries. While the first contrast is apparently broadly consistent with current institutionalist arguments about the impact of linkages between training systems and labour markets, the explanation for the deviation of the Southern European case is wanting. The results suggest both the need to incorporate additional institutional aspects into current transition research, but also stress the limitations of typological approaches in explaining crossnational differences in transition processes more generally." (author's abstract, IAB-Doku)
Keywords: G 1.3.2.2.3 Zweite Schwelle, in Arbeit; G 1.2 Arbeitsmarkt; S System beruflicher Bildung; S 1.3 Berufliche Erstausbildung; I 2.2 Europa; Berufseinmündung; Internationaler Vergleich; Arbeitsmarktindikatoren; Berufsbildungssystem; Quantitative Angaben; Europäische Union